Financial, Occupational and Physical Challenges and Blood Glucose Monitoring in Type 2 Diabetes - Jacob Marvin; Nicolette Powe (SAGE Publishing, 2023)
Background Blood glucose monitoring effects are changing for people living with type 2 diabetes. However, there is a lack of recent data surrounding financial, occupational, or physical stressors that affect the adherence of diabetes self-management practices. This article looks to examine specific financial, physical, and occupational challenges in adherence to blood glucose monitoring in type 2 diabetes. Methods Data from the National Health and Nutrition Examination Survey (NHANES) 2017-2020 Pre-Pandemic data of adults 18+ were analyzed. These data were used to examine the relationships between insurance coverage, health status, occupation, and self-monitoring of blood glucose levels in the United States. Results This study found that respondents had a statistically significant association with five variables: prescription drug coverage (in-part or full), occupation status, gender, age, and three race subcategories (non-Hispanic White, Black, and Other-Multiracial) with blood glucose monitoring. Conclusion This study may help certified health education specialists (CHES) and diabetes care and educator specialists (DCES) to better identify which groups of individuals are at highest risk for poor adherence to specific blood glucose monitoring in type 2 diabetes.